2016
DOI: 10.1016/j.jid.2015.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Contact Allergy to p-Phenylenediamine in the European General Population

Abstract: Population-based studies on contact allergy to p-phenylenediamine (PPD) are scarce. A cross-sectional study was performed to assess the prevalence of contact allergy to PPD and its risk factors in the general population of 5 European countries. A total of 10,425 subjects were interviewed, and a random sample (n = 2,739) was patch tested to PPD. Overall, 5,286 individuals (50.9%) reported having used hair colorants at least once in their lifetime (78% female, 20% male), and 35% had used hair colorants during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 29 publications
4
71
2
4
Order By: Relevance
“…27,28 Though we identified PPD and hair colours as the predominant contact sensitizers amongst our patient population having dermal hyperpigmentation, the type of antigens can vary depending upon the skin phototype, geographical localization and cultural practices of the studied population. 37 This especially holds true in Indian population where the application of henna tattoos is a common cultural practice. Moreover, even if subtle eczema does develop, it is difficult to discern the pinkness of skin in darker phototypes III-VI.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Though we identified PPD and hair colours as the predominant contact sensitizers amongst our patient population having dermal hyperpigmentation, the type of antigens can vary depending upon the skin phototype, geographical localization and cultural practices of the studied population. 37 This especially holds true in Indian population where the application of henna tattoos is a common cultural practice. Moreover, even if subtle eczema does develop, it is difficult to discern the pinkness of skin in darker phototypes III-VI.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalences of contact allergy in both the general and the patch tested population remain high, at 1.3% and 3.3%, respectively, in the population of The Netherlands . Diepgen et al reported a similar prevalence, namely 0.8%, in the general population of Europe .…”
mentioning
confidence: 96%
“…In the past 10 years, natural henna has been mixed with additives such as p ‐phenylenediamine (PPD), coffee or black tea, lemon juice, eucalyptus and clove or mustard oil to obtain a darker colour in the applications, and the new mode of this application, called ‘temporary black henna tattoo’, has become very popular in holiday resort areas. Although pure henna is relatively safe, with only a few reports of allergic reactions, black henna tattoos have been increasingly reported as a cause of allergic skin reactions , because PPD is known as a potent contact allergen . Although PPD is limited in hair dye to 2% calculated as free base , it is still being found in unregulated temporary black henna products at alarming levels ranging up to 64%.…”
mentioning
confidence: 99%